Use of immobilized lipase in cleaning up soil contaminated with oil (World Journal of Experimental Biosciences, 2016)
Thirty five isolates of Pseudomonas spp were obtained from seventy samples of soil contaminated with crude oil. The ability of lipase production by these isolates was screened. Pseudomonas ps 12 isolated from oil contaminated soil showed the highest lipase production (60 U/mg). This isolate was identified by VITEK-2 compact as a strain of P Pseudomonas aeruginosa. Lipase extracted from P. aeruginosa ps 12 was immobilized by adsorption on solid surface included charcoal and sawdust. The effect of enzyme (free and immobilized) on degradation of oils was studied into polluted soils. It was observed that the immobilized enzyme was more effective in removing oil than the free enzyme. The analysis of the heavy crude oil fractions was performed by Fourier Transform Infrared Spectroscopic (FTIR) technique to check the changes in their structure before and after treatment with P. aeruginosa ps 12 lipase. The result revealed that the spectra of crude oil treated with P. aeruginosa after 96 h of incubation many compounds disappeared and CO2 was released. This change indicated degradation of oil to simple structure and it is possible to use lipase producing from these isolates in treatment of soils and polluted environments to reduce the harm on soil.